PENGEMBANGAN MEDIA BIG BOOK BERBAHASA JAWA BABASAN BANTEN BAGI ANAK USIA 5-6 TAHUN (Pengembangan Model di PAUD Taman Yunior, Kota Cilegon, Banten) - Fajri Falah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2018)
Bahasa Java Babasan Banten is one of the most endangered regional languages. As one effort to preserve the language of Java Babasan Banten, this study was conducted with the main purpose of Java ledger book Babasan Banten in PAUD Junior High School Group B in Citangkil Subdistrict, Kota Cilegon, Banten. This research is an adapted development research from various research and development steps of Borg and Gall. The stages in the development of multimedia learning Java Javanese ledger Babasan Banten is doing preliminary research, making design, initial material development, validation by materials experts and media and media improvement as a reference for material and media position for. The resulting media was then discontinued eligibility by early childhood learning media experts, Kebanten’s figures and classroom teachers. The result of the research indicates that the media of Java Babasan Banten ledger are eligible with some improvements in terms of language, media layout and storyline.